Association of Body Mass Index with Angiographic Severity of Coronary Artery Disease in Patients with Acute ST- Segment Elevation Myocardial Infarction (Cardiovascular Journal, 2017)
Background: This study evaluated the association of body mass index (BMI) and angiographic severity of coronary artery disease in patients with acute ST segment elevation myocardial infarction (STEMI).Methods: Data were analyzed from 100 acute STEMI patients who underwent coronary angiogram. The patients were grouped based on BMI; those with normal BMI, 18.5- 24.9 kg/m2 (group I) and those with increased BMI, >25 kg/m2 (group II). Each group contained 50 patients. Angiographic severity of the three groups was compared and the relation between BMI and angiographic severity was assessed.Results: The mean BMI of subjects with normal angiographic findings was 20.81 ± 1.03 kg/m2. The mean BMI of single, double and triple vessel disease were 23.85 ± 2.24, 24.25 ± 2.41 and 32.06 ± 7.86 kg/m2 respectively. The number of vessel involvement increased in proportion with increased BMI and the differences were statistically significant (p=0.001).Conclusion: Increased BMI is associated with angiographic severity of coronary artery disease in patients with acute ST-segment elevation myocardial infarction.Cardiovasc. j. 2017; 10(1): 68-73